Halide perovskite materials as light harvesters for solar energy conversion. Issue 1 (January 2020) - Dong, Chao Ran; Wang, Yue; Zhang, Kan; Zeng, Haibo
Highlights: Recent progress in halide perovskite materials for solar energy conversion is summarized. Atom, crystal and device engineering for enhancing solar harvesting is highlighted. Challenges and future development in solar to fuel conversion are pointed out. Abstract: Due to the unsustainable fossil fuels, those conventional energy sources are diminishing and getting expensive. Since sun can provide insolation levels of 150–300 W/m², or 3.5–7.0 kWh/m² per day in most of the world's population live in areas, efficient utilization of the enormous energy source is continued to pursue. Solar energy can be usually harvested in a couple of different ways, among which harvesting solar energy by photon absorption in band gap materials and the subsequent collection of photo-induced charge carrier has been actively explored as promising strategy to store the abundant energy source. Halide perovskite materials, having optically high absorption characteristics and balanced charge transport properties, are considered a most potential light harvester to photovoltaics, as well as for solar energy conversion. Compared to charge transport, light harvesting capability is a must for high conversion efficiency of solar energy. In this review, we summarize the recent research progress in enhancing and modulating light harvesting capability of halide perovskite for PV devices and solar to fuel conversion from the perspectives of atomic level, crystal film level and device level, respectively. Graphical abstract: The review introduced some popular strategies for the light harvesting enhancement in the halide perovskite solar cells from different levels, including band gap engineering in atom level; modulation of crystal structural, plasmonic resonance, optical structure in crystal level and optical design in device level. Image, graphical abstract